Employee Being Undervalued at Work: A Phenomenological Study - Walter, Anthony Joseph (2012)
This qualitative study investigates employees’ experiences associated with the feeling or situation of being undervalued at work. The aim of this qualitative research is to understand the phenomenon of employees being undervalued at work. An in-depth study using the Hermeneutical Phenomenological approach was used to unfold and uncover the feeling of those involved. A recording of one-to-one interview was made on nine participants holding various ranking positions and from various industries in the natural work setting to attain the perspective of being undervalued at work and it constitutes the primary data for this research. The major findings such as boreout (BURNOUT), deviant behaviour, career ceiling, distrustful propensity, domineering tendency, wage distress, withdrawal behaviour and the spill over of job dissatisfaction to family domain indicating implications of employees’ being undervalued. This research reveals several events in developing human capital approaches as these contribute to authenticate appreciation for human resources development, and creates a real meaning, sense of belonging, deeper sense of collaboration and partnership with the organization. The researcher upholds the originality of this work with full pride and honesty for current and future improvement and development, paving ways for future research to continue to fill in the body of knowledge gap. The research contributes to guide Human Resources Development (HRD) practitioners to encourage the management of organizations to cultivate and embrace a holistic approach for the purpose of fostering values in every employee’s perception towards his or her work, peers, superiors and more importantly the employer. Employee satisfaction and recognition, as well as greater performance and retention can be achieved if employees are treated as assets, rather than taken for granted.